Genetic diversity in barley (Hordeum vulgare) for traits associated with feed and forage purposes - SARKAR, B; SARKAR, A; SHARMA, R C; VERMA, R P S; SHARMA, I (The Indian Journal of Agricultural Sciences, 2014)
Barley (Hordeum vulgare L.) is an important coarse cereal cultivated in many parts of the world since ancient times and mostly used as cattle & poultry feed. However, in India due to climate change and frequent drought especially in drier areas barley offers a better alternative to extreme climate such as drought and winter. In the present study 220 cultivated barley accessions of indigenous and exotic origin were evaluated for different agro-morphological traits. The material was evaluated during the 2011-12 growing season at DWR, Karnal where observations were recorded on 13 agro-morphological traits. The results showed high variability among the accessions for grain per spike, green fodder yield, grain yield, grain yield of regenerated crop, biological yield and harvest index (HI). Based on K-mean clustering pattern, the genotypes were grouped into five clusters having significant inter-cluster distances. Shannon-Weaver’s diversity index (H) and Simpson’s index (1/D) was used to assess the phenotypic diversity of traits for each cluster genotypes and overall. Shannon’s diversity index revealed large diversity for most traits. The average H for the whole population was 0.91 with the lowest 0.74 for HI, the highest (1.01) for days to heading. The simple correlation coefficients among traits were estimated, which showed significant positive relations between grain yield with plant height (r = 0.25**), green fodder yield (r = 0.15*), grain yield of regenerated crop (r = 0.13*) and HI (0.19**), while negative correlation with days to heading (r = –0.35**). Sources for individual traits in different genotypes of barley clusters were identified which can be used as donors in hybridization programme for dual purpose barley improvement programme.